Peran Pengantar Matematika Modern dalam Meningkatkan Kemampuan Berfikir Analitis Mahasiswa - Prihaten Maskhuliah; Aulia Zaskia Ramadhani; Alfredo Aditya Nugroho; Muklis Rivandi (Pentagon : Jurnal Matematika dan Ilmu Pengetahuan Alam, 2026)
Analytical thinking is an essential cognitive skill for university students in the digital era, and formal mathematics provides an important context for developing logical and systematic reasoning. This study examines the effectiveness of formal mathematics-based learning interventions in improving students’ analytical thinking skills. A Systematic Literature Review was conducted following the PRISMA protocol by identifying and selecting quantitative empirical studies from reputable scientific databases based on predetermined inclusion and exclusion criteria. The findings show that formal mathematics interventions, particularly structured proof-construction activities, significantly improve students’ cognitive performance (p < 0.05). The most notable gains were found in the ability to differentiate premises and organize axiomatic structures. Nevertheless, epistemological obstacles remain a major challenge, accounting for up to 42% of the variance in students’ reasoning scores. These difficulties are mainly associated with the high intrinsic cognitive load caused by the abstract nature of formal mathematics, which may lead to misconceptions when not properly managed. Therefore, educators and curriculum developers should design adaptive learning materials and gradual instructional strategies that reduce cognitive load while preserving the logical-deductive rigor of formal mathematics.